Heat Transfer of a non-Newtonian MHD boundary layer fluid flow with active and passive controls of nanoparticles - Noor, N.F.M.; Ramly, N.A. (2018)
In this paper, active and passive controls of nanoparticles in a Sisko fluid flow are considered. An external magnetic force is applied normal to the stretching surface beneath the non-Newtonian flow. The governing equations of the model in the form of partial differential equations, are later transformed to a set of nonlinear ordinary differential equations (ODEs) using suitable similarity variables. A numerical scheme is employed to solve the ODE system. The flow velocity, temperature and nanoparticles profiles are examined. The heat transfer of the flow is analysed. Comparison between the effects of active and passive controls of nanoparticles in the non-Newtonian flow is also discussed.